Knowledge, attitudes and utilization of food labels among undergraduate medical students in a medical college in Chennai - A cross sectional survey - Sinthiya Annamalai; Vijayaprasad Gopichandran (Wolters Kluwer Medknow Publications, 2022)
Introduction: Food labeling is an important method of providing food-related information on the package of food products, to facilitate people's choice of safe and appropriate foods. Medical students are potential agents of change in food label utilization behavior in the community. The objectives of this study were to evaluate the knowledge, attitudes, and utilization of food labels among undergraduate medical students in a medical college in Chennai. Material & Methods: We conducted a cross-sectional survey of 200 students studying in the 1st to 3rd year in a medical college through an online Google Forms survey, self-administered by the students after online informed consent was obtained. We gathered information on their knowledge, attitudes, and utilization of food labels. Results: Of 400 students approached, 200 responded to the online survey. They had good knowledge about food labels. Female students had 3.4 (1.59 to 7.25) times better knowledge compared to men. The students had a positive attitude toward food labels, and a majority thought that the food labels are useful. Utilization of food labels to understand the nutritive content (55%), additives (57%), and manufacturer details (47%) was poor. Utilization of food labels was 2.7 times more (1.142-6.587) among those who did regular exercise, and it was 0.2 (0.09 to 0.9) times less among those who were on a strict diet. Conclusion: Medical students had a sound knowledge and good attitude toward food labels, but their food label utilization patterns were still poor. There is a need to incorporate food labeling in the undergraduate medical curriculum and inculcate better food label utilization behavior.